2013
DOI: 10.1039/c2nr32760k
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescent ribonuclease-A-encapsulated gold nanoclusters: preparation, characterization, cancer targeting and imaging

Abstract: Ultra-small gold nanoclusters (AuNCs) have unique size-dependent optical, electrical and chemical properties. They have emerged as a new nanomaterial with broad applications in optoelectronics, catalysis, biosensing, and bioimaging. Several strategies have been exploited to prepare AuNCs of different "magic number" sizes, using different templates e.g. dendrimers, polyethyleneimines, peptides, and more recently, proteins. Notwithstanding, almost all bio-template-protected AuNCs reported so far exhibit fairly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 77 publications
1
84
1
Order By: Relevance
“…Currently, considerable research efforts are directed towards investigation of Au NCs synthesis [4][5][6][7][8][9][10], structure [7,11,12], optical properties [4,[13][14][15][16], photostability [17][18][19][20][21] and possible applications for material sensing [5,[22][23][24] as fluorescence [25,26] and dual-modality imaging contrast agents [27,28]. However, colloidal stability, photostability, dependence of optical properties on temperature, interaction of BSA-Au NCs with biomolecules are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, considerable research efforts are directed towards investigation of Au NCs synthesis [4][5][6][7][8][9][10], structure [7,11,12], optical properties [4,[13][14][15][16], photostability [17][18][19][20][21] and possible applications for material sensing [5,[22][23][24] as fluorescence [25,26] and dual-modality imaging contrast agents [27,28]. However, colloidal stability, photostability, dependence of optical properties on temperature, interaction of BSA-Au NCs with biomolecules are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Shichibu et al [12] observed that Au 13 clusters obtained by treating a polydisperse sample with hydrochloric acid show an emission band at 766 nm by excitation at 360 nm. Shibu et al [13] prepared Au 15 trapped in cyclodextrins showing the maximum emission centered at 690 nm when excited at 375 nm. Biang et al [14] synthesized luminescent Au clusters with a bright red emission and large Stokes shift using both histidine and 11-mercaptoundecanoic acid as stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Biang et al [14] synthesized luminescent Au clusters with a bright red emission and large Stokes shift using both histidine and 11-mercaptoundecanoic acid as stabilizers. Gold clusters were also obtained using ribonuclease A as bio-template showing a large Stokes shift (210 nm) and a high luminescence quantum yield (QY) of 12%, being suitable for cancer targeting and imaging [15]. In the described cases the authors did not investigate the reasons for the observed luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Tseng's group presented a novel approach for preparing highly fluorescent Au 8 NCs and Au 25 NCs by using lysozyme type VI (Lys VI) at pH 3 and pH 12, [43] respectively [49]. Inspired by this finding, researchers try to explore other proteins as efficient bioscaffolds for synthesizing AuNCs such as insulin [50], transferrin-family proteins [51,52], horseradish peroxidase [53], pepsin [54], denatured BSA [55], ribonuclease A [56], trypsin [57], DNase I [58], ovalbumin [59], and egg white [60].…”
Section: Proteinsmentioning
confidence: 99%